2020
DOI: 10.20944/preprints202001.0381.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2019 Novel Coronavirus: Where We are and What We Know

Abstract: There is a current worldwide outbreak of a new type of coronavirus (2019-nCoV), which originated from China and has now spread to 17 other countries. Governments are under increase pressure to stop the outbreak spiraling into a global health emergency. At this stage, preparedness, transparency and sharing of information are crucial to risk assessments and beginning outbreak control activities. This information should include reports from outbreak sites, and from laboratories supporting the investigation. This … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
183
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(198 citation statements)
references
References 19 publications
2
183
1
11
Order By: Relevance
“…Moreover, the higher perception of greater risk of COVID-19 infection by women is perhaps because the study included many health professionals who are at higher risk since the health sector's workforce is predominantly female. However, infection by COVID-19 seems to have a gender preference 32,33 . Chen et al found a higher number of men infected by COVID-19 than women.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, the higher perception of greater risk of COVID-19 infection by women is perhaps because the study included many health professionals who are at higher risk since the health sector's workforce is predominantly female. However, infection by COVID-19 seems to have a gender preference 32,33 . Chen et al found a higher number of men infected by COVID-19 than women.…”
Section: Discussionmentioning
confidence: 98%
“…The city of Fortaleza had a thousand deaths in a single day in a smallpox epidemic that occurred in 1868 17,35 . People of all ages can be infected with coronavirus 33 . In this study, the group aged 20-39 years considered having a high risk of infection (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From SARS in 2003 to H5N1 in 2004, from Influenza A (H1N1) in 2009 to COVID-19 in 2019, it is reported that new acute respiratory infectious diseases are the ones having the highest mortality. 2,3 Due to the COVID-19 is highly contagious, widespread and there is no specific drug, 4,5 medical workers are facing hitherto unknown challenges in both physical and men-vestigators.…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus disease 2019 (COVID-19) global pandemic is associated with a high estimated case-fatality rate of around 3.5% [1][2][3][4][5]. The main clinical feature of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is represented by bilateral pneumonia with radiological signs of ground glass opacification [6].…”
Section: Introductionmentioning
confidence: 99%